1997
DOI: 10.1006/dbio.1996.8413
|View full text |Cite
|
Sign up to set email alerts
|

Genes Required for GLP-1 Asymmetry in the EarlyCaenorhabditis elegansEmbryo

Abstract: The translation of maternal glp-1 mRNA is regulated both temporally and spatially in the early Caenorhabditis elegans embryo (T. C. Evans, S. L. Crittenden, V. Kodoyianni, and J. Kimble, Cell 77, 183-194, 1994). To investigate the control of embryonic glp-1 expression, we have examined the distribution of GLP-1 protein in selected maternal effect mutants that affect pattern or fate in the early embryo. We find that mutants that disrupt anterior-posterior asymmetry in the early embryo (par-1-par-6, emb-8, Par(q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This finding supports our model, because ectopic POS-1 in the anterior blastomeres would be expected to suppress translation. However, Crittenden et al (Crittenden et al, 1997) reported that in par-1 embryos, GLP-1 was detected in all blastomeres, in a manner similar to pos-1 embryos. We examined POS-1 expression in par-1(RNAi) embryos, and found that POS-1 was abundant in all blastomeres (data not shown).…”
Section: A Model For the Translational Regulation Of Maternal Glp-1 Mmentioning
confidence: 95%
“…This finding supports our model, because ectopic POS-1 in the anterior blastomeres would be expected to suppress translation. However, Crittenden et al (Crittenden et al, 1997) reported that in par-1 embryos, GLP-1 was detected in all blastomeres, in a manner similar to pos-1 embryos. We examined POS-1 expression in par-1(RNAi) embryos, and found that POS-1 was abundant in all blastomeres (data not shown).…”
Section: A Model For the Translational Regulation Of Maternal Glp-1 Mmentioning
confidence: 95%
“…Several genes required for different aspects of glp-1 regulation have been identified in mutant screens. Genes that control early cell polarity are necessary for GLP-1 localization in the embryo, presumably because they regulate the activities or localization of glp-1 regulators (Crittenden et al, 1997;Rose and Kemphues, 1998). In addition, two functionally redundant proteins, MEX-5 and MEX-6, act downstream of polarity genes and promote GLP-1 expression in anterior embryonic cells (Schubert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The transition zone is characterized by the appearance of crescent-shaped nuclei indicating differentiation into leptotene/zygotene of meiotic prophase I. Under normal conditions a wild-type adult worm has approximately 22–23 germ cell diameters (CD) between the DTC and the appearance of a small population of leptotene/zygotene nuclei (Crittenden et al, 1997). We found that the proliferative mitotic zone decreased from approximately 22 cell diameters (CD) in the control worms down to 14–15 CDs in the 24-hour feeding experiment (Figure 6).…”
Section: Resultsmentioning
confidence: 99%